Clinical observation of external application of compound Baiyu powder in treating cracked nipples during lactation period and related nursing management (复方白玉散外敷治疗哺乳期乳头皲裂临床疗效观察及护理) - CHEN Shuangshuang (陈双双); WANG Yuan (王媛); YOU Tingli (游婷李); CHEN Juan (陈娟) (中西医结合护理)
Objective To investigate the effect of external application of Traditional Chinese Medicine compound Baiyu powder in treating cracked nipples during lactation period, and summarized related nursing measures during treatment. Methods A total of 120 women with cracked nipples during lactation period were randomly divided into group A, group B and control group, with 40 cases in each group. The group A received external application of compound Baiyu powder, group B received external application of protective cream, and the control group received routine care during lactation period. The healing conditions of cracked nipples 5 days after intervention and breastfeeding rate were observed, and intervention effect was evaluated and compared among three groups. Results The total response rate was 97. 44%(38/39) in the group a, which was higher than 68. 42%(26/38) in group B and 40. 00% (16/40) in control group(P＜0. 05 respectively). A shorter time to pain relief and healing of cracked skin were observed in group A than those in group B and control group, respectively(P＜0. 01). The breastfeeding rate in the group A was higher than that in group B and control group, respectively (P<0. 05). Conclusion The external application of compound Baiyu powder is effective to improve the healing of cracked nipples without affecting milk production. Based on the theory of removing slough and promoting growth of tissue regeneration, nursing interventions by Traditional Chinese Medicine syndrome differentiation on regulation of dietary, emotion, daily routine and physical constitution should be carried out. (目的 研究中药复方白玉散外敷治疗乳头皲裂的效果, 总结护理措施。方法 按照信封法将120例哺乳期乳头皲裂产妇随机分为干预A组、干预B组和对照组, 各40例, 干预A组外敷复方白玉散, 干预B组外涂乳头保护霜, 对照组仅给予常规护理措施。观察三组5 d内乳头皲裂愈合情况和住院期间纯母乳喂养情况, 评价临床疗效。结果 干预A组临床总有效率97. 44%(38/39), 高于干预B组的68. 42%(26/38)和对照组的40. 00% (16/40), 差异有统计学意义(P＜0. 05)。干预A组止痛时间和皮损愈合时间较干预B组和对照组缩短(P＜0. 01)。干预A组住院期间纯母乳喂养率高于干预B组和对照组(P<0. 05)。结论 中药复方白玉散具有明显的促进乳头皲裂愈合及止痛作用, 且治疗期间不影响哺乳。在实施常规护理的同时给予中医辨证施护, 基于“祛腐生肌”理论使用中药外敷, 结合调理饮食、调畅情志、调理作息、改善体质, 对治疗乳头皲裂有重要意义。)